Invasive and non-invasive aesthetic procedures: risks and benefits (Research, Society and Development, 2023)
Introduction: Self-esteem is the positive or negative feeling people have about themselves. As a trainer and/or complementer of self-esteem, aesthetics emerges, a practical method compared to others, and capable of changing and/or enhancing the concept of beauty that exists in each person. It should be noted that, among the aesthetic procedures, which in itself encompasses many aspects, there are many issues to be considered, directed to the preoperative period, psychological preparation, intraoperative, postoperative, alignment of expectations, benefits, and risks, that, as with any procedure, it must be duly explained to the patient who wishes to undergo such an aesthetic procedure, whether invasive or not. Objective: to conduct a literature review on aspects related to the risks and benefits of invasive and non-invasive aesthetic procedures. Materials and methods: A descriptive and exploratory study was carried out based on a literature review, through research and collection of scientific data organized through the investigation of articles associated with the object of study. Results: Through the study, it was possible to elucidate the main differences between invasive and non-invasive cosmetic procedures, as well as their main risks and benefits.